Pharmacological chaperone therapy for lysosomal storage diseases. (June 2014) - Parenti, Giancarlo; Moracci, Marco; Fecarotta, Simona; Andria, Generoso
Pharmacological chaperone therapy is an emerging approach to treat lysosomal storage diseases. Small-molecule chaperones interact with mutant enzymes, favor their correct conformation and enhance their stability. This approach shows significant advantages when compared with existing therapies, particularly in terms of the bioavailability of drugs, oral administration and positive impact on the quality of patients' lives. On the other hand, future research in this field must confront important challenges. The identification of novel chaperones is indispensable to expanding the number of patients amenable to this treatment and to optimize therapeutic efficacy. It is important to develop new allosteric drugs, to address the risk of inhibiting target enzymes. Future research must also be directed towards the exploitation of synergies between chaperone treatment and other therapeutic approaches.